Democratic values in Balinese traditional society: Analysis of the making and the content of Desa Pakraman’s awig-awig - IGP Bagus Suka Arjawa; IGA Mas Rwa Jayantiari (Faculty of Social and Political Science, Universitas Airlangga, 2017)
This article describes the existence of democracy at a traditional level in Desa Pakraman in Bali. In Balinese society, Desa Pakraman is the root of social life, where people make interaction in culture and religion. Desa Pakraman is an organization underlies the life of Balinese society. Desa Pakraman has traditional instrument, called awig-awig. Awig-awig is an instrument of customary law in the society where the people have to obey the norms of the traditional law institution. Democratic practices and norms are apparent when people at Desa Pakraman build the awig-awig. Freedom of opinion can be found when people deliver their opinion we can find the equality of the human being. The research held in Desa Pakraman Penyalin, Tabanan, Bali, with qualitative method research. This research used democratic theory and participant theory. The research found that democracy has been practised at traditional society in Bali especially when people build the instrument of customary law. In Bali, this is called awig-awig. The awig-awig contains democratic instruments like equality before the law, human right and regular election to vote Desa Pakraman’s officials.